Economic burden of drug-induced anaphylaxis: what can we do better?. Issue 4 (August 2022) - Cardoso, Barbara; Moscoso, Teresa; Morais-Almeida, Mário; Demoly, Pascal; Tanno, Luciana K.
Abstract : Purpose of review: This systematic review evaluates published data related to the economic burden of drug-induced anaphylaxis (DIA) to understand preventive cost saving measures that could reduce the burden of these conditions. Recent findings: Although DIA has a relevant societal impact, there are limited and heterogenous available data related to its cost. Direct costs related to the management of acute phase of DIA was estimated by 529.6 to 3125, depending on the number of emergency room visits/hospitalizations, emergency kits and transports in ambulance. Direct costs of investigations of DIA varied from 288 to 2292.95 and the desensitization was estimated by 6796. Main variables for this were: personnel, allergy screening procedures, medical consumables and space cost. The mean indirect cost was based on a mean absenteeism of 3 days per DIA corresponding to 381.2. Summary: More than reviewing the published data, we were able to identify variables that, if correctly managed, can reduce the economic burden of DIA, such as adjusting the timing of referral and etiological diagnosis, identification of potential risk and/or co-factors, correct written recommendations to patients. The evidence presented highlights the need of optimization of healthcare patients to patients suffering from DIA.